Synthesis and biological evaluation of thiophene and benzo[b]thiophene analogs of combretastatin A-4 and isocombretastatin A-4: A comparison between the linkage positions of the 3, 4, 5-trimethoxystyrene unit. Issue 1 (1st January 2016) - Do, Cong Viet; Faouzi, Abdelfattah; Barette, Caroline; Farce, Amaury; Fauvarque, Marie-Odile; Colomb, Evelyne; Catry, Laura; Berthier-Vergnes, Odile; Haftek, Marek; Barret, Roland; Lomberget, Thierry
Graphical abstract: Abstract: Combretastatin A-4 and isocombretastatin A-4 derivatives having thiophenes or benzo[ b ]thiophenes instead of the B ring were prepared and evaluated for their in cellulo tubulin polymerization inhibition (TPI) and antiproliferative activities. The presence of the benzo[ b ]thiophene ring proved to have a crucial effect as most of the thiophene derivatives, except those having one methoxy group, were inactive to inhibit tubulin polymerization into microtubules. The influence of the attachment position was also studied: benzo[ b ]thiophenes having iso or cis 3, 4, 5-trimethoxystyrenes at position 2 were 12–30-fold more active than the 3-regioisomers for the TPI activity. Some of the novel designed compounds exhibited interesting anti-proliferative effects on two different cell lines.